Design and Development of an Innovative E-Bike. (November 2016) - Abagnale, C.; Cardone, M.; Iodice, P.; Marialto, R.; Strano, S.; Terzo, M.; Vorraro, G.
Abstract: A new model of power-assisted bicycle has been designed, set up and tested. The main innovative solutions for the pedelec prototype are described in the present paper: the electric motor position; the new mechanical transmission; the low cost measurement system of the driving torque; the special test rig. Differently from a common approach, in which the electric motor is located on one of the three hubs of the bicycle, the idea of the pedelec prototype consists of an electrical motor in the central position that, by means of a bevel gear, transmits the torque on the central hub. The other innovative solution is represented by the motion transmission from the motor to the pedal shaft, achieved by two different gearboxes: the first one is a planetary gearbox and the second one is a simple bevel gear. The pedelec prototype contains also a new low cost measurement system of the driving torque based on a strain gauge load cell located on one side of the rear wheel, between the hub and the frame. Moreover, a commercial cycling simulator has been suitably modified in order to properly install the different sensors for the measurement of the performance of the pedelec. The test rig is able to reproduce an aforethought route or paths acquired during road tests, to measure the performance of the e-bike in terms of instantaneous power and speed. The experimental test rig can simulate the resistant torque of a predetermined track and it aims to test and to optimize the control strategy available on the electronic control unit. The authors have also conducted an environmental analysis of the developed pedelec, in particular comparing the e-bike with a thermal moped, in terms of environmental impact.